Combining ability of yellow maize (Zea mays) inbred lines for yield and agronomic traits - ISMAIL, MOHAMMAD R; MOHAMED, HANY A A; ABD-ELAZIZ, MOHAMED A A; ABOYOUSEF, HESHAM A (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during 2021 and 2022 at Field Crops Research Institute, Agricultural Research Centre, Giza, Egypt to estimate combining ability effects of newly developed 8 yellow maize (Zea nays L.) inbred lines using diallel cross fashion. The 28 maize hybrids were obtained by half diallel crosses at Ismailia Research Station in 2021 and evaluated at 3 locations, viz. Ismailia, Sids and Sakha Research stations in 2022 for yield and agronomic traits. Experimental results revealed that crosses mean square was significant for all the studied traits. Similarly, general and specific combining ability were significant for all the traits. Parental line P8 considered to be an excellent combiner for all traits studied except for, number of days to 50% silking and number of rows characters. The hybrid P5 × P8 possessed desirable SCA effects for a great number of studied traits. Besides, it recorded the heighest mean value for grain yield (12.55 t/ha) plus lowest ear position. As result, this cross P5×P8 could be recommended for releasing after extensive evaluation.